Was wittgenstein a fideist? two views - McGovern, Ken (Sophia, 2002)
Kai Nielsen and Felicity McCutcheon have each in their own way taken issue with the received view that Wittgenstein’s remarks on religious language are to be construed as a form of “fideism”. They each provide sharply divergent views on Wittgenstein’s remarks on the meaning of religious language and, indeed, the importance of religion itself. These differences, however, serve to bring into relief both Wittgenstein’s recognition of the genuinely descriptive nature of ordinary religious discourse and his underlying political sensitivity. The paper reflects on these differences in the the recent works of Nielsen and McCutcheon on Wittgenstein’s alleged fedeism., “…speak the old language… but speak it in a way that is appropriate to the modern world, without on that account necessarily being in accordance with its taste.” (Wittgenstein, 1980, 60e)